Obesity epidemiology - Hu, Frank B. (New York ; Oxford : Oxford University Press, 2008)
This work offers practical information about the methodology of epidemiologic studies of obesity. The first section considers the definition and measurement of obesity and the designs of epidemiologic studies, while the next two sections address the consequences and determinants of obesity.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Obesity -- United States -- Epidemiology; Obesity -- Complications; Obesity -- Risk factors; Obesity -- Research